PENGARUH PENERAPAN VIDEO PEMBELAJARAN TERHADAP MOTIVASI BELAJAR SISWA KELAS X PADA MATA PELAJARAN BAHASA INDONESIA DI SMA NEGERI 5 KOTA CILEGON - Atho, Athoullah; Desty Endrawati Subroto; Kurniati Rahmadani (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2025)
The aim of this research is to find out how much influence Learning Videos have on Learning Motivation at SMAN 5 Cilegon. The research method used in this research is a descriptive method using a quantitative approach. The place of this research is at SMAN 5 Cilegon, with a population of 225 students, and the number of samples in this research is 75 students. The results of the analysis of the coefficients show that the correlation coefficient value shows that the rxy coefficient value is 0.549, so it is stated in the medium category, and rtable is 0.227. rcount > rtable = 0.549 > 0.227. The results of the t test obtained a tcount value of 5.608 while ttable was 1.66600 with an error level of 5%, thus tcount > ttable = 5.608 > 1.66600, so it can be concluded that the correlation coefficient between Learning Videos on Learning Motivation has a positive and significant effect and from the hypothesis testing that has been carried out Ho is rejected and Ha is accepted. The coefficient of determination (cd) is obtained at 30%, based on the causal or causal nature of this variable relationship, a simple linear regression equation can be created, namely Y = a + bX, a= 13,452, while the value of b is b = 0.527 Keywords: Learning Video Media, Student Learning Motivation